Reflections on aspects of music interactivity in performance situations - Lindborg, PerMagnus (2011)
Music interactivity is a sub-field of human-computer interaction studies. Interactive situations have different degree of structural openness and musical “ludicity” or playfulness. Discussing music seems inherently impossible since it is essentially a non-verbal activity. Music can produce an understanding (or at least prepare for an understanding) of creativity that is of an order neither verbal nor written. A human listener might perceive beauty to be of this kind in a particular music. But can machine-generated music be considered creative and if so, wherein lies the creativity? What are the conceptual limits of notions such as instrument, computer and machine? A work of interactive music might be more pertinently described by the processes involved than by one or several instanciations. While humans spontaneously deal with multiple process descriptions (verbal, visual, kinetic…) and are very good at synthesising, the computer is limited to handling processes describable in a formal language such as computer code. But if the code can be considered a score, does it not make a musician out of the computer? As tools for creative stimulus, composers have created musical systems employing artificial intelligence in different forms since the dawn of computer music. A large part of music interactivity research concerns interface design, which involves ergonomics and traditional instrument maker concepts. I will show examples of how I work with interactivity in my compositions, from straight-forward applications as composition tools to more complex artistic work.